Psychological predictors of life satisfaction among undergraduates (2013)
Informed by previous research finding which established evidence of low satisfaction among undergraduates in Nigeria, the purpose of this paper was to examine the psychological variables that would predict satisfaction with life among undergraduates in Southwestern Nigeria. A cross-sectional ex post facto survey design was adopted and convenient sampling method was used. Three hundred and twenty (118, i.e. 36.9%) male and 202 (63.1%) female students, ages ranging between 16 to 27 years (M = 28.47, SD = 8.76) participated in this study. Validated scale was used for data collection and the hypothesis stated was confirmed after testing with appropriate statistics. The result showed that NaCh and Hloc significantly predicted satisfaction with life among undergraduates, whereas, anxiety was not a significant predictor. Internals who were high on need achievement were low on satisfaction with life, while externals who were low on need achievement were high on satisfaction with life. Conclusion was reached that professional services would be required for undergraduates with low satisfaction with life in order to orientate them regarding adjustment and coping with reality of life in order to prevent psychological breakdown. A limitation to this is study would be the small sample size and the limited psychological variables that were examined. However, further research may make these a focus.